Penegakan Hukum terhadap Kasus Pelanggaran Izin Usaha Pertambangan (IUP) pada Pertambangan Nikel - Kanda Ramandana (Savana, 2024)
Mining is an activity that is very complex or very complicated in its implementation because not everyone can do it because it also deals with nature. If you don't pay attention to the natural ecosystem, it will damage nature, therefore mining such as mineral mining which is non-renewable energy or cannot be renewed. Permits must be prepared before carrying out mining analysis and production. The aim of the research is to analyze the regulation and law enforcement in cases of violations of mining business permits in nickel mining. The research method used in this research is descriptive-analytic with a juridical-normative type of research. The results of regulatory research are in Article 158 of Law Number 3 of 2020 concerning amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining that: "Every person who carries out a mining business without a Mining Business Permit (IUP), People's Mining Permit ( IPR) or Special Mining Business Permit (IUPK) as intended in Article 37, Article 40 paragraph (3), Article 48, Article 67 paragraph (1), Article 74 paragraph (1) or paragraph (5) shall be punished with a maximum imprisonment 10 (ten) years and a maximum fine of IDR 10,000,000,000.00 (ten billion rupiah).” Law enforcement, namely in court decision decision no. 296/ Pid.Sus/ 2021/ PN Kdi, PT Kreasi Lippo In its decision, namely, sentencing the defendant to prison for 7 (seven) months and a fine of Rp. 1,000,000,000,- (One Billion Rupiah) with the provision that if the fine is not paid it will be replaced by imprisonment for 2 (two) months. The conclusion is that at the time of its realization law enforcement against illegal miners was still relatively light